Participatory land resources planning to promote sustainable landscape management in rainfed areas-Morocco - Ziadat, Feras; Berkat, Omar; Ouchna, Rochdi; Touami, Mouna; Fetsi, Theodora; Harari, Nicole; Studer, Rima Mekdaschi; Schlingloff, Stefan (Frontiers in Sustainable Food Systems, 2022)
Land degradation and desertification affect around one-third of the land used for agriculture and about 1.5 billion people worldwide, undermining productivity, and farmers’ livelihoods, and resilience. People in rainfed and dryland areas are the most vulnerable to the environmental and social impacts of degradation, yet opportunities to expand agricultural areas in order to meet the needs of an ever-growing population are limited and/or not feasible. On the bright side, there are opportunities to reverse this trend, however, it will require identifying areas that are suited to implement sustainable land management (SLM) practices and create an enabling environment that encourages such initiatives. In Morocco, data from 2015 showed that 19 percent of its land over the total land area is degraded. In order to assess the level of degradation in rainfed landscapes of Morocco and identify the appropriate technological solutions in response to the driving forces and pressures, analyses were carried out at different levels to identify the land degradation hot spots as well as the SLM bright spots. This paper sheds light on the decision support framework, co-developed with partners and applied in Morocco, the findings from national and subnational assessments of land degradation using the LADA-WOCAT methodology, as well as the process of participatory planning in selected communities of the Souss-Massa region for evaluation and scaling up of SLM good practices. The process led to the development of a “territorial planning pact” as a tool for land use planning and a three-year action plan to help decision-makers implement and mainstream SLM in the selected communities and guide similar processes throughout the region. The “territorial planning pact” forms a base for planning and implementing the development program in the region led by key stakeholders. The paper presents the actions taken and concludes by highlighting the importance of integrating both biophysical and socio-economic information in a multi-level participatory process to identify the actions and responsibilities of various stakeholders and ensure sustainable management of limited natural resources and improved livelihoods for all.